Analysis of Passenger Satisfaction at Husein Sastranegara Airport - R. Indra Crisna Seputra; Juliater Simarmata (Dinasti International Journal of Management Science, 2024)
The article analyzing passenger satisfaction at Husein Sastranegara Airport is a scientific literature review article within the scope of marketing management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of human resource management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The findings of this research are as follows: 1) The check-in process influences passenger satisfaction at Husein Sastranegara Airport; 2) Airport accessibility influences passenger satisfaction at Husein Sastranegara Airport; and 3) Transportation connectivity influences passenger satisfaction at Husein Sastranegara Airport.